2006
DOI: 10.1182/blood-2006-04-016980
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing immunotherapy in multiple myeloma: restoring the function of patients' monocyte-derived dendritic cells by inhibiting p38 or activating MEK/ERK MAPK and neutralizing interleukin-6 in progenitor cells

Abstract: Previous studies demonstrated that circulating dendritic cells (DCs) in myeloma patients were functionally abnormal. However, the phenotype and function of patients' monocyte-derived DCs (MoDCs), which are commonly used for immunotherapy, were poorly defined. This study was undertaken to examine the quality of MoDCs from myeloma patients compared with cells from healthy donors. We found that patient-derived MoDCs are phenotypically and functionally defective. Compared with their normal counterparts, patient-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
1
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 38 publications
7
61
1
5
Order By: Relevance
“…Similar observations were made in the murine 5TGM1 MM model in which an inhibition of DC differentiation and function by MM cells via IL-6, IL-10, and TGF-β and activation of p38 mitogen-activated protein kinase (MAPK) signaling have been reported [54]. This inhibitory mechanism was confirmed in monocyte-derived DCs from myeloma patients and p38 inhibition resulted in a restoration of DC function [55]. Restoring or ensuring normal DC function might be of great interest for several cellular immunotherapy approaches that depend on it.…”
Section: Dendritic Cellssupporting
confidence: 67%
“…Similar observations were made in the murine 5TGM1 MM model in which an inhibition of DC differentiation and function by MM cells via IL-6, IL-10, and TGF-β and activation of p38 mitogen-activated protein kinase (MAPK) signaling have been reported [54]. This inhibitory mechanism was confirmed in monocyte-derived DCs from myeloma patients and p38 inhibition resulted in a restoration of DC function [55]. Restoring or ensuring normal DC function might be of great interest for several cellular immunotherapy approaches that depend on it.…”
Section: Dendritic Cellssupporting
confidence: 67%
“…[68][69][70] In MM, the monocyte-derived DCs generated by the patients are functionally defective; this was found to be due to cytokines released by MM cells. 71 TLR ligands may amplify these effects and inhibit DC maturation. Although recent reports show that Treg-cell function can be inhibited by directly targeting TLR8, 72 studies using other TLR ligands have observed enhanced Treg-cell induction and improved Treg-cell function.…”
Section: Tlr Activation Of Both Immune and Neoplastic Cells: How To Smentioning
confidence: 99%
“…Detailed protocol was described previously. 19 Primer sets used for these analyses were as follows: RAR␣1 forward, 5Ј-CCA TCT AGG AGT GGC ATC TTT T, reverse, 5Ј-ACT AAC TGG AAG CTG GTG CTG; RAR␣2 forward, 5Ј-GAG GAG GAA GTG CTC GTT GAC, reverse, 5Ј-GCC CGG TTC TGG TTA TAA AAA T; and GAPDH forward, 5Ј-GAC ACC CAC TCC TCC ACC T, reverse, 5Ј-ATG AGG TCC ACC ACC CTG T. GAPDH transcript levels were used to normalize the amount of cDNA in each sample. …”
mentioning
confidence: 99%